2011
DOI: 10.1002/sres.1120
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Framework for Multiparadigm Multimethodologies

Abstract: The multimethodological practice of systemic intervention has been described as 'theoretically contradictory eclecticism' because it lacks a grounding theory that can accept Burrell and Morgan's principle of incommensurable paradigms and avoids 'anything goes' relativism between them. As a way forward, a new ontology of process-structure is proposed. It is designed as a metaphysical interface to the onto-epistemological paradigms of critical systems thinking and practice (which are, in this paper, functionalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Of course, it is possible that reflexive practitioners may (re)deploy the concepts presented here to legitimate defective management, but so also is the possibility that they may help clients, stakeholders, end-users and project practitioners, to be more cautious, more hesitant, and hopefully more ethical, when giving or receiving interpretations of project "failure" (or "success"). Following Pollack (2006) we do not deny onto-epistemological incommensurability, but suggest different theoretical approaches can be minimally compatible when addressing such practical, and we add here political, matters of concern (see also Bowers, 2011). We advocate theoretical pluralism as a means of introducing plurality as a political intervention against functionalistpositivist/managerial orthodoxy, while recognizing the limitations of pluralism as a methodology to develop more substantive analysis (especially within the confines of a single research paper).…”
Section: Concluding Commentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Of course, it is possible that reflexive practitioners may (re)deploy the concepts presented here to legitimate defective management, but so also is the possibility that they may help clients, stakeholders, end-users and project practitioners, to be more cautious, more hesitant, and hopefully more ethical, when giving or receiving interpretations of project "failure" (or "success"). Following Pollack (2006) we do not deny onto-epistemological incommensurability, but suggest different theoretical approaches can be minimally compatible when addressing such practical, and we add here political, matters of concern (see also Bowers, 2011). We advocate theoretical pluralism as a means of introducing plurality as a political intervention against functionalistpositivist/managerial orthodoxy, while recognizing the limitations of pluralism as a methodology to develop more substantive analysis (especially within the confines of a single research paper).…”
Section: Concluding Commentsmentioning
confidence: 95%
“…As a result, despite the general acceptance of the plurality of managerial rationalities (Hotho and Pollard, 2007), the plurality of modes of organization (Morgan, 1997), and the plurality of global politics (Dussell and Labarra-Collado, 2006), critical, but theoretically pluralistic work has been rare, either as an empirical (Hassard, 1991) or review-based (Davila and Oyon, 2007) contribution. And yet, there continues to be a steady, if diffuse, stream of calls for theoretical pluralism, as an aid to reflexive critical thinking across the social sciences (Bohman, 1999;Healy, 2003), as well business-related fields such as critical systems thinking (Bowers, 2011;Mingers and Brocklesby, 1997;Pollack, 2006), which continue to influence project management. By contrast, for many aligned with CMS, the position on the theoretical fence appears full of splinters: by adjudicating amongst distinct theoretical approaches, authors construct a specious meta-theoretical view (see e.g.…”
Section: Theoretical Pluralism Revisitedmentioning
confidence: 99%
“…Paradigm incommensurability figuratively could be presented in the following way: "groups of scientists relying on different paradigms see different things when they look from the same point in the same direction" [6] (p. 149). Hence, it can be concluded that paradigms are self-sufficient, internally referential and mutually exclusive [26]. On the other side, Mingers [27] makes several arguments against a strong view of paradigm incommensurability, such as:…”
Section: A Conceptual Framework For Combining the Systems Methodologiesmentioning
confidence: 99%
“…The Burrell and Morgan model (1979) became a classic in paradigmatic studies of social theories, prompting research and discussions, which led to the proliferation of criticism of the model (i.e., Bowers, 2011;Deetz, 1996). An important criticism is that this model served the purpose of reification of approaches.…”
Section: Subjectivist Approach To Social Sciencesmentioning
confidence: 99%
“…Despite some discomfort caused by its philosophical dimensions and analyses, researchers skilled in approaches and methods other than those identified as mainstream felt recognized and legitimated by the classification scheme proposed by these authors, as well as those who were mainstream and were subjected to scathing criticism (Atkin, Hassard, & Cox, 2007;Bowers, 2011;Deetz, 1996;Morgan 1983).…”
mentioning
confidence: 99%